TRAINING GUIDANCE OF STRATEGIC PLAN PREPARATION PROCESS AT BAPPEDA AGENCY OF SAROLANGUN REGENCY - Ardi Afrizal; Faizal Riza; Nurdin Nurdin (LPPM Universitas Muhammadiyah Jambi, 2025)
The purpose of mentoring training on the strategic planning process (rencana strategis) of Sarolangun Regency is to improve understanding of the program and activity plans for the next five years which are contained in the vision, mission, goals, targets, and strategies that will be used as guidelines for implementing all program activities in a structured, measurable and targeted manner. Mentoring activities use face-to-face training methods. The results of this training mentoring are a form of community service, especially in the regional development planning agency of Sarolangun Regency, where the results of the mentoring are that all participants can understand the process of compiling and how the rencana strategis works which will be a reference for the program